Simultaneous integrated boost within the lymphatic drainage system in breast cancer: A single center study on toxicity and oncologic outcome - Klusen, Sophie T.; Peiler, Antonia; Schmidt, Georg P.; Kiechle, Marion E.; Muench, Stefan; Asadpour, Rebecca; Combs, Stephanie E.; Borm, Kai J. (Frontiers in Oncology, 2023)
Background and purpose In breast cancer patients, the increasing de-escalation of axillary surgery and the improving resolution of diagnostic imaging results in a more frequent detection of residual, radiographically suspect lymph nodes (sLN) after surgery. If resection of the remaining suspect lymph nodes is not feasible, a simultaneous boost to the lymph node metastases (LN-SIB) can be applied. However, literature lacks data regarding the outcome and safety of this technique. Materials and methods We included 48 patients with breast cancer and sLN in this retrospective study. All patients received a LN-SIB. The median dose to the breast or chest wall and the lymph node system was 50.4 Gy in 28 fractions. The median dose of the LN-SIB was 58.8 Gy / 2.1 Gy (56-63 Gy / 2-2.25 Gy). The brachial plexus was contoured in every case and the dose within the plexus PRV (+0.3-0.5mm) was limited to an EQD2 of 59 Gy. All patients received structured radiooncological and gynecological follow-up by clinically experienced physicians. Radiooncological follow-ups were at baseline, 6 weeks, 3 months, 6 months and subsequent annually after irradiation. Results The median follow-up time was 557 days and ranged from 41 to 3373 days. Overall, 28 patients developed I°, 18 patients II° and 2 patients III° acute toxicity. There were no severe late side effects (≥ III°) observed during the follow-up period. The most frequent chronic side effect was fatigue. One patient (2.1 %) developed pain and mild paresthesia in the ipsilateral arm after radiotherapy. After a follow-up of 557 days (41 to 3373 days), in 8 patients a recurrence was observed (16.7%). In 4 patients the recurrence involved the regional lymph node system. Hence, local control in the lymph node drainage system after a median follow-up of 557 days was 91.6 %. Conclusion If surgical re-dissection of residual lymph nodes is not feasible or refused by the patient, LN-SIB-irradiation can be considered as a potential treatment option. However, patients need to be informed about a higher risk of regional recurrence compared to surgery and an additional risk of acute and late toxicity compared to adjuvant radiotherapy without regional dose escalation.